Ferroptosis, a novel pharmacological mechanism of anti-cancer drugs - Su, Yanwei; Zhao, Bin; Zhou, Liangfu; Zhang, Zheyuan; Shen, Ying; Lv, Huanhuan; AlQudsy, Luban Hamdy Hameed; Shang, Peng (Cancer letters, 2020)
Ferroptosis, a form of regulated cell death, is initiated by oxidative perturbations of the intracellular microenvironment, which is under the constitutive control of glutathione peroxidase 4 (GPX4). Ferrous iron (Fe2+) accumulation and lipid peroxidation are critical events in the induction of ferroptosis, which is inhibited by iron chelators and lipophilic antioxidants. Ferroptosis terminates in mitochondrial dysfunction and toxic lipid peroxidation. It plays a vital role in inhibiting cancer growth and proliferation. It can be induced in cancer cells, and certain normal cells, by experimental compounds (e.g., erastin, Ras-selective lethal small molecule 3) or clinical drugs. The purpose of this review is to summarize the various drugs (e.g., sulfasalazine, lanperisone, sorafenib, fenugreek (trigonelline), acetaminophen, cisplatin, artesunate, combination of siramesine and lapatinib, ferumoxytol, and salinomycin (ironomycin)) that could induce ferroptosis in cancer cells and provide an overview of current knowledge regarding the mechanisms underlying ferroptosis. In future, we anticipate the development of more ferroptosis-inducing drugs, and the availability of such drugs for the clinical treatment of cancer. •We listed ten anticancer drugs related to ferroptosis.•We focused on the novel mechanisms of pharmacology of ten drugs.•We summarized all the current mechanisms related to ferroptosis.